Exploring the implementation of the TIME Home Learning programme and learning trajectories of 5- to 7-year-olds The TIME programme in its ecosystem: How can provincial education departments support the implementation and success of TIME? - von Blottnitz, Magali (Wordworks, 2024)
This is the second in a series of learning briefs that explore the implementation of the TIME Home Learning programme and the learning trajectories of 5- to 7-year-olds. This brief is based on interviews held in 2022 with the Western Cape Education Department’s (WCED) Head Office and district officials. It focuses on the role of provincial education departments in supporting the TIME programme and examines: - How the WCED contributed to incubating the TIME programme during the COVID-19 pandemic; - Strategic alignment between TIME and the WCED; - The role of Foundation Phase subject advisors; - Constraints and Opportunities in the WCED's support of the TIME programme; - and Implications for other provinces.
TIME Learning Brief no 2
More information about the TIME (Together in My Education) home-learning programme and materials can be found in open access at: https://wwhomeliteracy.org.za/time/
Keywords: Early learning; Early literacy; South Africa; Wordworks; Home-learning; Parental involvement; Grade R; Grade 1; Foundation Phase; Education Department; Subject advisor